2015
DOI: 10.1021/acs.langmuir.5b00646
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Bovine Serum Albumin (BSA) at the Oil/Water Interface: A Neutron Reflection Study

Abstract: The structure of the adsorbed protein layer at the oil/water interface is essential to the understanding of the role of proteins in emulsion stabilization, and it is important to glean the mechanistic events of protein adsorption at such buried interfaces. This article reports on a novel experimental methodology for probing protein adsorption at the buried oil/water interface. Neutron reflectivity was used with a carefully selected set of isotopic contrasts to study the adsorption of bovine serum albumin (BSA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 37 publications
4
31
0
Order By: Relevance
“…Water/fluid interfaces are structurally simpler and therefore particularly well suited to give unambiguous results. NR studies on liquid/liquid interfaces involving thin water or oil films on planar solid substrates [48,49,50,51,52,53,54,55] usually used partially deuterated oils and/or H2O/D2O mixtures, were aimed at characterizing organic interfacial layers rather than the bare interfaces, and will be discussed further below.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Water/fluid interfaces are structurally simpler and therefore particularly well suited to give unambiguous results. NR studies on liquid/liquid interfaces involving thin water or oil films on planar solid substrates [48,49,50,51,52,53,54,55] usually used partially deuterated oils and/or H2O/D2O mixtures, were aimed at characterizing organic interfacial layers rather than the bare interfaces, and will be discussed further below.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The variety of studies found in literature include not only monolayers of surfactants of different chemical nature (e.g. lipids 13 , asphaltenes 4 , proteins 5,6 and polymers 7 ) but also of solid particles (nanoparticles, particles in the colloidal size range and larger) 8,9 . While one of the bulk liquid is usually water the other liquid phase can be volatile solvents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…17). Neutron reflection has enabled molecular models of protein adsorption to be constructed, 18 has been used to determine the orientation of antibodies non-specifically adsorbed at the solid/liquid interface, 19 and has yielded the structural characterization of membrane proteins in bilayer models resting on a water-filled layer. 20 Current approaches to mitigate chemical and physical instabilities require the addition of buffers and excipients to mAb formulations.…”
Section: Introductionmentioning
confidence: 99%